Assessing the Multifaceted Determinants of Collaborative Competence Among Students in the Digital Learning: A Comprehensive Analysis - Saputra, Indra; Sari, Resti Elma; Mahniza, Melda; Hayatunnufus, Hayatunnufus; Rahmiati, Rahmiati; Yanita, Merita; Yupelmi, Mimi (JOIV : International Journal on Informatics Visualization, 2024)
The study background related to the students' collaborative competence in digital learning is still relatively low. The objective of this study is to examine the elements influencing collaborative competence. The study involved 107 cosmetology and beauty education students. The method used was a survey with data collection using questionnaires developed based on predetermined variable indicators. The analysis of data employed Structural Equation Model-Partial Least Square (SEM-PLS) with Smart PLS 4.0 software. The SEM results describe the Convergent Validity (Loading Factor and Average Variance Extracted) and Discriminant Validity (Fornell Larcker Criterion and Cross Loading), which states that the measurement model is valid. Furthermore, the Composite reliability and Cronbach's Alpha conclude that the measurement model is reliable. The analysis results indicate a positive and significant correlation of predictor variables, including project-based learning, social media, instructional approach, and material relevance to collaborative competence. Based on the variable analysis, material relevance becomes the highest aspect, followed by project-based learning, which increases the collaborative competence of students. Conversely, social media as a mediator variable weakens the level of correlation of the predictor variables to collaborative competence. This study contributes to understanding factors affecting students' collaborative competence in digital learning environments, with significant implications for educators, institutions, and policymakers in shaping digital learning frameworks enhancing collaborative competence. Future research, including longitudinal studies, could investigate the lasting impact of digital learning environments on developing collaborative competence over time.